83.1k views
0 votes
If x = -2 and y = 12, thеn 2(3х3 + 2у2) =
ОАО
о в 12
о с 48
ооо
oo 96

2 Answers

5 votes

Answer:

528

Explanation:

2(3х³ + 2у²)

Where x = -2 and y = 12 which means whenever you sees x, put -2 in replacement and y put 12

So we solve;

2(3x³ + 2y²), x = -2, y = 12

2[3(-2)³ + 2(12)²]

2[3(-8) + 2(144)]

2[-24 + 288]

open the bracket by multiplying by 2

-48 + 576

combine

528

User Chouquette
by
4.5k points
5 votes

Answer:
=528

Explanation:

You have this expression:


2(3x^3 + 2y^2)

You already know that the value of the variable "x" is:


x=-2

And the value of the variable "y" is:


y=12

Therefore, you can substitute the value of the variable "x" and the value of the variable "y" into the expression.

Then you get:


2(3(-2)^3 + 2(12)^2)=2(-24+288)=2(264)=528

User Glenny
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.